Strategi Kurikulum 2013 Dalam Mengembangkan Daya Kritis Generasi Z - Al Manaf; Tasman Hammami (Instructional Development Journal, 2020)
Tujuan penelitian ini untuk  mengetahui dan menganalisis strategi kurikulum dalam mengembangkan daya kritis generasi Z. Hal ini disebabkan adanya tantangan masa depan yang kompleks berkaitan dengan globalisasi dan pasar bebas, masalah lingkungan hidup, kemajuan teknologi informasi, konvergensi ilmu dan teknologi, ekonomi yang berbasis pengetahuan, kemajuan industri kreatif dan budaya, pengaruh teknosains, mutu, investasi dan transformasi pada sektor pendidikan. Penelitian ini menggunakan pendekatan Library Research dengan melakukan kajian literatur. Adapun hasil penelitiannya ialah kurikulum 2013 sebagai rancangan yang digunakan dalam masa teknologi demi terciptanya generasi teknolog yang berperan baik dalam dunia nyata maupun dalam dunia maya sebagai penerus generasi bangsa dan kemajuan bangsa itu sendiri. Strategi yang digunakan dalam mengembangkan dan membentuk daya kritis.The purpose of this research is to find out and analyze curriculum strategies in developing critical power generation Z. this is due to complex future challenges related to globalization and free markets, environmental problems, advances, in information technology, convergence, of science and teechnology, knowledge based economics, the advancement of creative and cultural industries, the influence of technology, quality investment and transformation in the education sector. This study uses the Library Research approach by conducting a literature review. As for the results of his research in the 2013 curriculum as a design that is used in the era of technology for the creation of a generation of technologists who play a role both in the real world and in cyberspace as the next generation of the nation and the progress of the nation it self. Strategies used in developing and shaping the critical power of students are Problem Based Learning as a method in helping children to develop thinking skills, overcome problems, investigation skills and the ability to learn the role of adults through involvement in real experiences or simulations and Cooperative Learning as a method that are constructivist in which students are demanded and build knowledge independently.